Geranylation of Cyclic Dipeptides and Naphthols by the Fungal Prenyltransferase CdpC3PT_F253G - Li, Dan; Wang, Yi; Xu, Yuanyuan; Long, Hongping; Min, Wenqing; Gao, Shangfeng; Li, Shu‐Ming; Yu, Xia (Chembiochem : a European journal of chemical biology, 2025)
Prenyl modification often improves the biological activities of compounds. Prenyltransferases have attracted attention as environmentally friendly biocatalysts for catalyzing prenyl modification of compounds. Compared to dimethylallyl modifications, research on geranyl modifications is relatively limited. To enrich biocatalytic toolboxes for generating potentially bioactive geranylated derivatives, this study developed methodologies to synthesize two types of geranylated compounds, i. e., geranylated tryptophan‐containing cyclic dipeptides and geranylated naphthols, employing the F253G mutant of CdpC3PT, a cyclic dipeptide prenyltransferase from Neosartorya fischeri. The cyclic dipeptides (1–3) were transformed into C7‐geranylated products (1G1–3G1), whereas 1‐naphthol (4) and derivatives (5–6) yielded C4‐geranylated products (4G1–6G1) and 2,7‐dihydroxynaphthalene (7) generated a C3‐geranylated product (7G1). All seven substrates and their geranylated products underwent antibacterial efficacy testing against Bacillus subtilis. Among them, five geranylated compounds (2G1 and 4G1–7G1) demonstrated antibacterial efficacies against Bacillus subtilis, with MIC values ranging from 4 to 32 μg/mL, surpassing their non‐geranylated precursors. This research broadens the tools of geranyl‐modifying biocatalysts, illustrates a case for developing highly efficient or function‐altered biocatalysts and showcases the potential of prenyltransferases in the biosynthesis of bioactive small molecules. The F253G mutation of CdpC3PT exhibited enhanced catalytic efficiency in geranylation of cyclic dipeptides and naphthols. The mutant's reaction specificity is towards C7‐geranylation of cyclic dipeptides, while 1‐naphthol and its derivatives were converted into C4‐geranylated products. Furthermore, five geranylated products (2G1 and 4G1–7G1) displayed antibacterial activity against Bacillus subtilis, with MIC values ranging from 4 to 32 μg/mL, surpassing their non‐geranylated precursors. This research broadens the range of geranyl‐modifying biocatalysts and highlights the potential for developing efficient or functionally modified biocatalysts.